2016
DOI: 10.2981/wlb.00244
|View full text |Cite
|
Sign up to set email alerts
|

Spring spotlight counts provide reliable indices to track changes in population size of mountain‐dwelling red deer Cervus elaphus

Abstract: Informazioni legaliL'istituto Superiore per la Protezione e la Ricerca Ambientale (ISPRA) e le persone che agiscono per conto dell'Istituto non sono responsabili per l'uso che può essere fatto delle informazioni contenute in questo rapporto. ISPRA - AutoriElisabetta Raganella Pelliccioni, Francesco Riga e Silvano Toso Luca Pedrotti ha collaborato alla stesura del capitolo dedicato al monitoraggio delle popolazioni. Stefano Mattioli e Vito Mazzarone hanno collaborato alla stesura del paragrafo relativo al cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 114 publications
(174 reference statements)
1
35
0
Order By: Relevance
“…Our results are consistent with those of Corlatti et al () who concluded that spotlighting was an effective method in heterogeneous landscapes capable of producing reliable indices of population abundance over time for red deer. McShea et al () and Beaver et al (), however, noted that sampling along roads that follow landscape features that structure animal populations violates critical assumptions for experimental designs and may bias the detection rates and subsequent density estimates for populations (Ward et al ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those of Corlatti et al () who concluded that spotlighting was an effective method in heterogeneous landscapes capable of producing reliable indices of population abundance over time for red deer. McShea et al () and Beaver et al (), however, noted that sampling along roads that follow landscape features that structure animal populations violates critical assumptions for experimental designs and may bias the detection rates and subsequent density estimates for populations (Ward et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Past efforts have evaluated environmental factors (e.g., weather, seasonal, land cover types) influencing spotlight counts (Progulske and Duerre , Rybarczyk , McCullough ), the accuracy of counts, and the precision of population indices (McCullough , Fafarman and DeYoung , Cypher , Whipple et al ). Although spotlight methods are capable of producing reliable indices of relative abundance for ungulates in some landscapes (Focardi et al , Garel et al , McShea et al , Anderson et al , Corlatti et al ), the effectiveness of spotlight counts to produce reasonable and precise estimates of density has remained inconsistent because of bias associated with study design, environment, or animal behavior (Focardi et al , McShea et al , Anderson et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Corlatti et al. ). In 4 yr, from 2011 to 2016, within the study site a total of 358 female deer (0.5 yr: n = 81; 1.5 yr: n = 39; 2+ yr: n = 238) were culled by professional hunters, under the supervision of the Park Authority.…”
Section: Methodsmentioning
confidence: 99%
“…External variables included population size in the previous spring (based on mark–resight estimates: Corlatti et al. ) and meteorological variables. On the Alps, deer fertilization occurs at the beginning of October, and fat reserves are mainly deposited in spring–summer: Because in this environment warmer temperatures are linked to anticipated vegetation growth (Pettorelli et al.…”
Section: Methodsmentioning
confidence: 99%